Deleites de la Cocina Mexicana = Healthy Mexican American Cooking - Urdaneta, Maria Luisa 1931-; Kanter, Daryl F. 1950- (Austin : University of Texas Press, 1996)
Gathers low-fat recipes for traditional Mexican dishes, including frijoles, chiles rellenos, enchiladas, fajitas, and tamales.
Includes bibliographical references (p. 225) and index.
aEnglish and Spanish.
Keywords: Diabetes -- Diet therapy; Mexican cooking; Low-fat diet